SAT0111 The Impact of Comorbidities and Extra-Articular Manifestations on 10-Year Mortality Risk in Rheumatoid Arthritis. Results from Two Multi-Centre UK Inception Cohorts. (9th June 2015) - Nikiphorou, E.; Demetriou, C.; Norton, S.; Walsh, D.A.; Dixey, J.; Kiely, P.; Sokka-Isler, T.; Young, A.
Abstract : Background: Comorbidity and extra-articular disease screening in Rheumatoid Arthritis (RA) is important as they impact negatively on disease outcomes and survival. Most RA observational studies have used generic indices such as the Charlson Comorbidity Index, or a simple comorbidity count. There is still no standardised, uncomplicated and validated instrument for collecting comorbidity data, relevant to contemporary and routine rheumatology practice. Objectives: To examine the predictive value of comorbidities & extra-articular manifestations by the first year of RA on 10-year mortality. Methods: The study was based on two multicentre (n=32) UK inception cohorts: the Early RA Study (1986-1999;n=1465) & Early RA Network (2002-2013;n=1236). Standard clinical, laboratory & radiographic variables were recorded at baseline & yearly intervals. Date/cause of death was provided by the Medical Research Information Service. The presence of comorbidities & extra-articular manifestations were grouped into the standard ICD10 systems (n=15) & further subdivided by severity, e.g. cardiovascular major (ischaemic heart disease [IHD], cardiac failure) or minor (benign cardiac arrhythmias). Multivariate Cox regression analysis adjusting for age at disease onset, gender, baseline BMI & presence of rheumatoid factor & recruitment year was used, with all-cause mortality as the outcome at 10 years. Results: 896 (33%) patients with RA had at least one major comorbidity; 472 had at least one minor recorded by the first year of disease (1yr prevalence of major/minor comorbidities=35%/18.5%). There were 849 (31%) deaths (total number person-years=34048). The commonest comorbidities recorded were hypertension (1yr prevalence =15.7%), diabetes & thyroid disease (9.7%), IHD (5.1%). Significant predictors of 10yr mortality by disease system are shown in the table . Examination at individual disease level revealed that IHD, chronic obstructive pulmonary disease (COPD) & renal/urological malignancies significantly predicted 10yr mortality when tested separately & together in multivariate models: renal/urological malignancies HR 2.34; COPD HR 2.28; IHD HR 1.71, all p<0.05. Other comorbidities like pulmonary embolism & cancers, specifically lung & G.I., Hodgkin's Lymphoma & metastatic disease showed significant predictive value but as the case numbers were low (<15) these were excluded from the final models. Major extra-articular manifestations (e.g. vasculitis, interstitial lung disease) had predictive value for 10yr mortality (HR 1.92, p=0.006) & from these, interstitial lung disease had the strongest predictive value (HR 2.69, p=0.011). Conclusions: Different comorbidities showed different predictive value for mortality in RA, with predominance seen with malignant disease. The best predictive model for 10yr mortality is the one that controlled for COPD, IHD and renal/urological malignancy, aside from standard demographic/patient variables. Further work is currently underway to develop a weighted comorbidity index based on these findings to be validated in the present & other cohorts. Disclosure of Interest: None declared